Emission estimates and inventories of non-methane volatile organic compounds from anthropogenic burning sources in India - Stewart, Gareth J.; Nelson, Beth S.; Acton, W. Joe F.; Vaughan, Adam R.; Hopkins, James R.; Yunus, Siti S. M.; Hewitt, C. Nicholas; Wild, Oliver; Nemitz, Eiko; Gadi, Ranu; Sahu, Lokesh K.; Mandal, Tuhin K.; et al. (Elsevier, 2021)
Comprehensive, spatially disaggregated emission inventories are required for many developing regions to evaluate the relative impacts of different sources and to develop mitigation strategies which can lead to effective emission controls. This study developed a 1 km2 non-methane volatile organic compound (NMVOC) emission model for the combustion of fuel wood, cow dung cake, municipal solid waste (MSW), charcoal, coal and liquefied petroleum gas (LPG) in India from 1993 to 2016. Inputs were selected from a range of detailed fuel consumption surveys and recent emission factors measured during comprehensive studies of local burning sources. For the census year of 2011, we estimated around 13 (5–47) Tg of NMVOCs were emitted from biomass and MSW combustion in India. Around 54% of these emissions were from residential solid biofuel combustion, 23% from open burning of MSW, 23% from crop residue burning on fields and <1% from LPG for cooking. NMVOC emissions from residential combustion were shown to be highly sensitive to the amount of cow dung cake combusted and this acted as a key pollution source across the Indo-Gangetic Plain. The results of this study indicate that multiple mitigation strategies are required across several different categories of burning source to achieve effective NMVOC emission reduction.
Keywords: Non-methane volatile organic compounds; India; Emission inventory; Burning; Residential combustion